Estrategias didácticas para la enseñanza de la Geografía en instituciones de educación básica (Investigaciones) - Mujica López, Ángel (2023)
Knowledge about how people learn and how to improve the teaching of scientific disciplines has meant a leap in education. One of the main aspects of improving pedagogical practice is didactic strategies. Therefore, this study aimed to propose a program of didactic strategies for teaching Geography at an educational institution in the Yaracuy state in Venezuela. It was a quantitative study in which three phases were developed: Phase I: Diagnostic Study, supported by descriptive field research. Phase II: Feasibility Study, and Phase III: Design of the Proposal) and in which 12 teachers of the basic education stage participated. The study applied a 16-item opinion questionnaire, validated by expert judgment, and Cronbach’s Alpha coefficient determined reliability. The results indicate the existence of a primary school teacher who is willing to participate in proposals and training programs in which they show alternatives of didactic strategies for the improvement of pedagogical practice, understanding the importance of educational institutions as a center to generate spaces for debate and training depending on their reality. In conclusion, the developed proposal has guiding purposes so that it can be applied, considering the realities of each educational context.